Correlation analysis of financial assets based on asymmetric copula - Li, Xia; Hou, Bing (Frontiers in Applied Mathematics and Statistics, 2022)
Based on the asymmetric Copula function, this paper analyzes the static and dynamic correlation between Shanghai Composite index and Shenzhen Composite index. Through the static analysis, it is found that the asymmetric Copula function is better than Gumbel Copula in describing the distribution characteristics of the top tail dependence between Shanghai Composite Index and Shenzhen Composite Index, and the Copula correlation coefficient definition based on the asymmetric Copula function can well describe the asymmetric dependence between variables. In the time-varying analysis, the paper improves the traditional dynamic evolution equation of tail dependence coefficient. Through empirical analysis, the result shows that the improved dynamic evolution equation can better reflect the dynamic evolution process of tail dependence coefficient.